2014
DOI: 10.1007/s13595-014-0443-8
|View full text |Cite
|
Sign up to set email alerts
|

Production and role of epicormic shoots in pruned hybrid poplar: effects of clone, pruning season and intensity

Abstract: Abstract• Key message Pruning one third of crown length in summer produced the least number of epicormic branches after two growing seasons. Epicormic branches can be removed without compromising tree growth.• Context The formation of epicormic shoots is often observed following pruning treatments, but their role in the overall tree growth is unknown.• Aims The objectives of this study were to examine how pruning intensity and season affect the production of epicormic branches and how their presence (or remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The proportion and absolute value of both the total reconstructed length and number of annual shoots composed by traumatic reiterations (TR) were greater in H trees than in M trees while the average TR length was similar. Consistent with previous findings [57][58][59][60][61], this suggests that the more heavily a tree was trimmed, the more numerous the TR. 1.…”
Section: Real-life Examplesupporting
confidence: 90%
“…The proportion and absolute value of both the total reconstructed length and number of annual shoots composed by traumatic reiterations (TR) were greater in H trees than in M trees while the average TR length was similar. Consistent with previous findings [57][58][59][60][61], this suggests that the more heavily a tree was trimmed, the more numerous the TR. 1.…”
Section: Real-life Examplesupporting
confidence: 90%
“…Based on the model, the authors derived the inference that in the early stages of plant growth, the ratio of biomass to demand increases and induces a fast increase in the growth unit size, which then stabilizes and oscillates due to the appearance of branches (Mathieu et al 2009). In concordance with our assumption, Desrochers et al (2015) found that hybrid poplar trees pruned to 2/3 crown length produced nearly twice as many epicormic branches with over twice the biomass of 1/3 pruned trees within 2 vegetation periods, which was interpreted as a means for trees to restore the balance between leaf area and non-photosynthetic organs. However, the specificities of our data deduce the tentative nature of the derived dendromass models and for this reason they must be viewed as preliminary.…”
Section: Modelling Rationalesupporting
confidence: 87%
“…Compared with other tree species, poplar has many characteristics that make it suitable for cultivating in plantations, enabling the production of large quantities of wood in short periods of time. These features consist of rapid growth, adaptability to diverse environmental conditions, and suitability for different silvicultural systems [ 1 3 ]. In China, poplars are usually cultivated at a density of 830–1100 trees per ha.…”
Section: Introductionmentioning
confidence: 99%